The order of things: An archaeology of the human sciences - Foucault, Michel (London Routledge, 2002)
When one defines "order" as a sorting of priorities, it becomes beautifully clear as to what Foucault is doing here. With virtuoso showmanship, he weaves an intensely complex history of thought. He dips into literature, art, economics and even biology in The Order of Things, possibly one of the most significant, yet most overlooked, works of the twentieth century. Eclipsed by his later work on power and discourse, nonetheless it was The Order of Things that established Foucault's reputation as an intellectual giant.